The Evolution of the European Union's Securitization of Climate Change and the Effectiveness of Its Policies (Journal of Education, Humanities, and Social Research, 2025)
As climate change intensifies as a pressing global concern, its securitization has become a pivotal issue in international governance. The European Union (EU), recognizing the escalating risks, has increasingly incorporated climate change into its security agenda, framing it as a non-traditional security threat. This paper explores the EU's securitization process through the framework of the Copenhagen School's Securitization Theory, examining its internal and external climate policies across discursive, institutional, and practical dimensions. Initially adopting a "rhetorical leadership" approach, the EU evolved towards "leadership-by-example" and, more recently, has assumed the role of a "leadiator", promoting global cooperation on climate initiatives. The paper evaluates the effectiveness of major EU policies, including emissions reduction commitments and the advancement of renewable energy, while also addressing persistent challenges such as internal policy fragmentation and external geopolitical pressures. The study concludes that although the EU's securitization of climate change has notably shaped global climate governance, significant obstacles remain in fostering deeper international collaboration and resolving internal inconsistencies.